Determinants of Duration of Untreated Psychosis in Patients with Schizophrenia in Indonesia - Darmawati; Habibillah, Isra Yusri Yanti; Marthoenis (Asian Journal of Public Health and Nursing, 2024)
Background: The duration of untreated psychosis (DUP) is a crucial factor influencing the prognosis of schizophrenia, affecting long-term outcomes and treatment efficacy. Despite its importance, there is a paucity of research on the determinants of DUP in Indonesian patients with schizophrenia, highlighting the need for a focused investigation within this specific context. This study aims to identify the determinants of DUP among patients with schizophrenia in Indonesia. Methods: A cross-sectional study was conducted involving patients with schizophrenia admitted to a referral psychiatric hospital in Indonesia. Data were collected using guided interviews and observations through structured questionnaires. Additionally, socio-demographic information was gathered. Results: A multiple linear regression analysis revealed that previous consultations with traditional healers (β = 21, 95% CI = 11.4 - 30.6, p = 0.001) and religious healers (β = 16.7, 95% CI = 8.2 - 25.2, p = 0.0001) were independently predicting the longer DUP. Conclusions:Treatment-seeking behavior is significantly influencing the DUP in patients with schizophrenia. Efforts should focus on improving health literacy to encourage earlier mental health treatment-seeking.